Molecular mechanisms of the Guizhi decoction on osteoarthritis based on an integrated network pharmacology and RNA sequencing approach with experimental validation - Chen, Yan; Xue, Yan; Wang, Xuezong; Jiang, Ding; Xu, Qinguang; Wang, Lin; Zheng, Yuxin; Shi, Ying; Cao, Yuelong (Frontiers in Genetics, 2023)
Background: To determine the potential pharmacological mechanisms of the Guizhi Decoction (GZD) in the treatment of osteoarthritis (OA) through an integrated approach of network pharmacological analyses, RNA-seq and experimental validation. Methods: The quality control and bioactive compounds of GZD by UPLC, and their OA-related genes were identified through overlapping TCMSP, DrugBank SEA databases and Genecards. GO and KEGG pathway analyses were implemented after conducting component-target network. RNA-seq was used to screen differentially expressed genes (DEGs) under the intervention condition with and without GZD in vitro. Accordingly, PPI networks, GO, and KEGG analysis were performed with Cytoscape, String or David database. OA rat model was established to further verify the pharmacological effects in vivo. HE and S-O staining were used to grade the histopathological features of cartilage. We verified the mRNA and proteins expression of key targets related to TNF signaling pathways in vivo and vitro by qPCR, WB, and IF. In addition, we also detected the inflammatory cytokines in the rat serum by Luminex Liquid Suspension Chip. Results: Eighteen compounds and 373 targets of GZD were identified. A total of 2356 OA-related genes were obtained. Three hub active ingredients of quercetin, kaempferol, and beta-sitosterol were determined, while 166 target genes associated with OA were finally overlapped. RNA-seq analysis revealed 1426 DEGs. In the KEGG intersection, the closest screening relevant to GZD treatment was TNF signaling pathway, of which TNF, IL-6, and IL-1β were classified as hub genes. In consistent, HE and S-O staining of rat model showed that GZD could attenuate cartilage degradation. Compared with OA group, the mRNA levels of inflammation genes and catabolic proteins in cartilage were all downregulated in the GZD group, while The expression levels of anabolic proteins were all higher in GZD group. In addition, the expression levels of TNF, IL-6, and IL-1β were upmodulated in the OA group, while GZD group prevented such aberrations. Conclusions: The present study revealed that the mechanism of GZD against OA may be related to the regulation of TNF signaling pathway and the inhibition of inflammatory response.